Enzymatic - enhanced production of gaharu oil : effects of shaking speed and water/ gaharu ratio - Sanisah, Arsat (2008)
Gaharu with scientific named Aquilaria is a very valuable plant where widely used for medicine, perfumery, and incense. Due to its rarity and the high growing demand for it, gaharu essential oil brings very high prices. One of the common methods to extract gaharu oil is by hydro distillation. However, the yield of gaharu oil using this method is still in small percentage. Previous researches proved that enzymatic hydrolysis during pre-treatment can give better result of gaharu oil yield extraction. Since enzymes are generally active over a specific range of reaction condition, research to improve the enzymatic hydrolysis has been conducted. Two parameters which are shaking speed (rpm) and water/gaharu ratio (v/w) that affect the enzymatic hydrolysis were studied. From the results, the yields for gaharu oil extraction were increased as the shaking speed increased from 50 rpm to 150 rpm. At the shaking speed of 200 rpm, the yield did not continue the same trend as the yield was decreased. The highest yield for varying rpm is 0.1092 at the 150 rpm. The yields for gaharu oil extraction were decreased due to the increasing water/gaharu ratio from 8:1 v/w to 20:1 v/w. The highest yield for varying water/gaharu ratio is 0.1092 at the ratio of 8: 1 v/w. Based on results obtained, the combination of 150 rpm and water/gaharu ratio of 8: 1 v/w during enzymatic hydrolysis pretreatment produced maximum gaharu oil yield extraction which is 0.1092%.